INCOME DISTRIBUTION AND THE FACTORS THAT INFLUENCE OF INCOME OF RUBBER FARlffiR IN SIGUNTUR VILLAGE, SITIUNG SUBDISTRICT DHARMASRAYA REGENCY - Eflita, Rita - (Pendidikan Ekonomi, 2014)
This  research  is to  analyse  of  income  distribution  and  the  factors that  influence  of income  of rubber  farmer  in  Siguntur  Village,  Sitiung  Subdistrict  Dharmasraya  Regency.  This Research  is descriptive associative.  The data of research are primary and secondary.  Amount of population  are 925 chairman of family and amount of sample which is taken  is 90 chairman of family.  A slovin formula till alternative take purposive  sampling. Data analyse is descriptive, Gini Ratio analyse of inductive which  consist  of model  reasonable  test,  classic assumption  test,  re!,>ressions  analyse, coefficient  of determinasi,  and  hypothesis test.  Gini Ratio  see high and  low disrtibusi  of people earning in Siguntur Village Sitiung Subdistrict Dharmasraya  Regency.  The result  of this research show condition of distribution decreasing of farmer earning in Siguntur Village Sitiung Subdistrict Dharmasraya  Regency the result of gini ratio 0,59 that mean distribution   of the farmer earning is located  in strong decreasing  category.  The result  of analysis  Regression  show  that  (1) Wide of farm  have  a  significant  to farmer  earning  in  Siguntur  Village  Sitiung  Subdistrict  Dharmasraya Regency where is value  thitung is 36,64 > ttabel  is 1,99 and the value sig is 0,000 < 0,05 it means HI  is received  HO is refused.  (2) a seed has a significant to farmer  earning in Siguntur Village Sitiung  Subdistrict  Dharmasraya  Regency  where  is the value thitung is 3,96 > ttabel is  1,99 and the value sig is 0,000 < 0,05 it means H2 is received HO is refused. (3) the kindness ofEnergy has a  significant  to  farmer  earning  in  Siguntur  Village  Sitiung  Subdistrict  Dharmasraya  Regency where  is thitung is 3,76  > ttabe/1,99  and  value  sig 0,000  < 0,05  it  means  H3  received  HO  is refused.  (4) the price has a significant  to farmer  earning  in  Siguntur Village  Sitiung Subdistrict Dharmasraya  Regency where is the value thitung is to 3,13 > ttabel  is 1,99 and the value sig 0,002< 0,05 it means H4 is received HO is refused (5) Wide Off arm, a seed, Kindness Energy and Price have significant totally about farmer earning in Siguntur Village  Sitiung Subdistrict DharmasrayaRegency where is the value Fhitung is 423,214 > Ftabel  is 2,47 and the value sig is 0,000 < 0,05, it means H5 is received HO is refused.